Efektivitas Bimbingan Kelompok Teknik Modelling Simbolis untuk Meningkatkan Efikasi Diri Siswa IX SMP Negeri 3 Baubau - Rasman Sastra Wijaya; Unhaluddin Thalib Kurniawan; Risma Irmayana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
The purpose of this study was to examine the effectiveness of group counseling services for effective symbolic modeling techniques to improve the self-efficacy of class IX students of SMP Negeri 3 Baubau. The experimental design used in this study was a one-group pretest and posttest design. The population in this study were 72 class IX students of SMP Negeri 3 Baubau, totaling 72 people consisting of 3 classes. The sample in this study was grade IX students of SMP Negeri 3 Baubau who had low self-efficacy as many as 13 students who were used as a sample of a treatment effectiveness test. Testing the validity of the self-efficacy scale using the Analyze Correlate Bivariate test through the help of a computer program statistics product and service solution (SPSS) 16.0 for windows. Known value of Z -3,185 with Asymp. Sig (2-tailed) value of 0.001 in this study is smaller than ˂ 0.05, it can be concluded that the Guidance Services Group of symbolic modeling techniques is effective to improve the self-efficacy of class IX students of SMP Negeri 3 Baubau which is done successfully significantly or effectively to be carried out , this means, the hypothesis is accepted